KEKERASAN DI SEKOLAH BAGIAN MASALAH PENDIDIKAN SOSIAL- EMOSIONAL - Sugiyatno, Sugiyatno (Paradigma, 2015)
Ballying in school happened not without of couse, but happened because accumulation from problemss in process of educations which have taking place. We cannot adjudg to one of aspect as source cause . One of alternative of which can be gone through for anticipating the happening of ballying in school is with looking for source of root of problem, that is revising function and role of education in family, school, and public. Third this component have to be powered in an optimal fashion, especially area of family, where role of parents in giving" affection" or education of social-emotional which recently don’t touch student. Any form of behavior of student in this time is result from education process which have taking place in this country, where parents, teacher and public held responsible. Keywords : education of social-emotional, family, school, public